On Some Numerical Radius Inequalities Involving Generalized Aluthge Transform. (1st September 2022) - Hyder, Javariya; Akram, Muhammad Saeed; Alofi, Abdulaziz S.; Akter, Dilruba
Abstract : Let S be any bounded linear operator defined on a complex Hilbert space H . In this paper, we present some numerical radius inequalities involving the generalized Aluthge transform to attain upper bounds for numerical radius. Numerical computations are carried out for some particular cases of generalized Aluthge transform.